Réponses

2014-01-05T10:25:34+01:00
Bonjour

a) 2x < 6
x < 6/2
x < 3
S = ]-infini ; 3[

b) 3x < -12
x < -12/3
x < -4 
S = ]-infini ; -4[

c) - 2x <32
x > 32/(-2)
x > -16
S = ]-16 ; + infini[

d) 2x > -8
x > -8/2
x > -4
S = ]-4 ; +infini[

e) - 2x > 6
x < 6/(-2)
x < -3 
S = ]-infini ; -3[

f ) - 4x > -28
x < (-28)/(-4)
x < 7
S = ]-infin ; 7[
2014-01-05T10:26:55+01:00
A) 2x <6
x<6/2
x<3

b) 3x<-12
x<-12/3
x<-4

c) - 2x <32
x>-32/2
x>-16

d) 2x > -8
x>-8/2
x>-4

e) - 2x > 6
x<-6/2
x<-3

f ) - 4x > -28
x<28/4
x<7